New appearance of social services within the scope of a new public administration approach - Yildirim, Arzu (IGI Global, 2021)
With the globalization process and the transition to the information society, change policies in public administration have emerged. In this context, many regulations were made in the 2000s. Participation, accountability, governance, and localization trends have gained importance in the provision of services. As a result of the new public administration approach, holding the non-governmental organizations, private sector, and local administrations responsible for the fulfillment of their duties and responsibilities gained momentum with the withdrawal of the state from the social sphere. The aim of the study is to evaluate the restructuring process that occurs in social services within the scope of restructuring studies carried out in the country. Within the scope of decentralization of services, social municipalism, which is the new aspect of localization of social services, will be emphasized. At this point, it is aimed to reveal the change in social services within the scope of the new public administration approach. © 2021, IGI Global.